An extended model for a punch through (PT) insulated gate bipolar transistor (IGBT) and its transient characteristics - Saif, Omar; Pavel, Md. Fazle Rabbi; Hasan, Md. Akib; Shah, Asif (BRAC University, 2017)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2017.